Surgery on displaced depressed skull fracture overlying sigmoid sinus: Rationale, techniques, and risk management - Kadek Biondi; Tjokorda Gde Bagus Mahadewa; Marleen (Indoscholar, 2022)
Skull fracture may occur at all parts of the skull after direct trauma. Skull fragment overlying dural venous structure, may inherit the risk of infection, thrombosis, and massive bleeding. Controversy arises among institutions whether the surgical measure is superior to the conservative option. The occurrence of depressed skull fracture overlying sigmoid sinus is seldom discussed in trauma literature, but some authors reported that the risk of infection and sepsis might occur in a delayed fashion in this group of patients. Several reports on the radiological study in depressed skull fracture overlying venous sinus found that fracture may predispose to venous sinus thrombosis. However, the risk of profuse bleeding when attempting to elevate bone fragments could place the patient into serious and devastating conditions, which need aggressive and effective bleeding control. We report a case of a middle-aged man who had a displaced depressed skull fracture overlying the right sigmoid sinus after falling from height. Surgery was performed in order to decompress the right sigmoid sinus structure and repair the cerebrospinal fluid leak at the overlying duramater. The patient was discharged from the hospital with minimal conductive hearing disturbance, with no sign of infection and neurologic deficits.